Extraction of Silica from Bengkulu Beach Sand using Alkali Fusion Method - Soraya Nur Ishmah; M. Diki Permana; M. Lutfi Firdaus; Diana Rakhmawaty Eddy (University of Bengkulu, 2020)
Silica is one of the potential minerals to be developed and applied in various industrial fields. High purity of silica can be obtained by utilizing natural materials such as beach sand. In this research the solid-liquid extraction (leaching) method was used in three main steps. Bengkulu beach sand as precursors reacted with NaOH (alkaline fusion) at 95°C to form Na2SiO3, then addition of HCl to form Si(OH)4, and drying the silica gel becomes SiO2. Based on the initial content analysis in Bengkulu sand contained 69.87% silica and other compounds with a lower percentage. The extracted silica was characterized using XRF and the purity of silica increase to 97.3%. The XRD characterization results showed that the silica formed was in the amorphous phase. Si-O-Si and Si-O bonds which are characteristics of SiO2 were identified in the FT-IR spectrum with absorption bands of 798.8 cm-1 and 475.1 cm-1 respectively.